Barrenness, Righteousness, and Marital Faithfulness in Luke 1:6-7, 25: Implications for Infertility Practices in West African Christian Communities - Oyeniyi, Oluseye David (Jurnal Ilmiah Tafsir Alkitab, 2026)
Barrenness in Gospel of Luke 1:6-7, 25 was examined as a pastorally significant issue with implications for marital faithfulness in African Christian communities, where infertility often carried social stigma and shaped marital expectations. Although Lucan scholarship had widely explored the infancy narrative, limited attention had been given to the theological significance of barrenness for infertility practices and marital ethics in African Christian contexts. This study therefore investigated Luke’s portrayal of barrenness, its relationship to covenantal righteousness and marital fidelity, and its relevance for contemporary ecclesial responses to infertility. A qualitative interpretive approach grounded in spiral hermeneutics was employed, integrating textual, narrative, and socio-historical analysis with African contextual and feminist theological perspectives. The findings show that Luke presents barrenness as compatible with righteousness and faithful marriage, thereby challenging assumptions that equate fertility with divine favour or marital legitimacy. The study concludes that Luke’s theology of barrenness provides a constructive biblical framework for compassionate, contextually grounded, and pastorally responsible engagement with infertility in African Christian communities.